London's waterfront 1100-1666 : excavations in Thames Street, London, 1974-84 - Schofield, John, 1948- (Archaeopress Publishing Ltd, 2018)
This volume presents and celebrates the mile-long Thames Street in the City of London and the land south of it to the River Thames as an archaeological asset. The argument is based on the reporting of four excavations of 1974-84 by the Museum of London near the north end of London Bridge: Swan Lane, Seal House, New Fresh Wharf and Billingsgate Lorry Park. Here the findings of the period 1100-1666 are presented.